Preventing online gambling through classical guidance services - Putri Ria Angelina; Reni Sinta Dewi; Noneng Siti Rosidah; Nur Asiah Ulfah (Jurnal Konseling dan Pendidikan, 2026)
The rapid advancement of technology has generated both beneficial and adverse consequences, with online gambling emerging as a growing concern among students. This study aimed to evaluate the effectiveness of classical guidance services in preventing online gambling behavior. A quasi-experimental approach with a one-group pretest–posttest design was employed, involving 20 students selected through purposive sampling. Data were collected using an online gambling behavior scale covering cognitive, affective, and behavioral aspects, which had been tested for validity and reliability. The data were analyzed using a paired sample t-test. The results revealed a significant difference between pretest and posttest scores, indicating that classical guidance services effectively reduced students’ tendencies toward online gambling behavior. These findings suggest that classical guidance can serve as a practical preventive intervention within school settings to address digital-risk behaviors among students.